DEVELOPMENT OF COMICS BASED LEARNING MEDIA IN CLASS 2 THEME 5 MATERIAL MY EXPERIENCE AT HOME - Destriana; Dian Nuzulia Armariena; Marleni (Universitas PGRI Palembang, 2024)
This research is motivated by the low interest in reading of students in learning Indonesian because in the teaching and learning process teachers tend to use tools in the form of media in the form of books only and lecture methods, making it less interesting for students to pay attention to. This research aims to determine the development of comic-based learning media that is valid, practical and effective for use in class 11 in Indonesian language subjects. This research was carried out at SD Negeri 17 Palembang which is located on Jl. Enim Lorok Pakjo, Demang Lebar Daun, Palembang City, South Sumatra. This research is a type of ADDIE research, namely analysis, design, development, implementation and evaluation. The population and sample in this research were class 2 students at SD Negeri 17 Palembang, totaling 30 students in the class. Data collection techniques in this research are observation, interviews, questionnaires and documentation. , The results of this research are the results of the assessment of all validators, the percentage is 98% with the criteria